2020
DOI: 10.1080/21691401.2020.1817054
|View full text |Cite
|
Sign up to set email alerts
|

Near-infra-red fluorescent chitosan oligosaccharide lactate for targeted cancer imaging and photothermal therapy

Abstract: Photothermal therapy (PTT) is a promising approach for effective cancer treatment because of its noninvasive procedure, low toxicity to normal tissues, and high tumour ablation efficiency. Developing a PTT agent with precise tumour imaging capabilities is an essential prerequisite for effective PTT. In this study, we developed a bifunctional near-infra-red (NIR) fluorescent conjugate consisting of chitosan oligosaccharide lactate (COL) and the ZW800-1 NIR fluorophore (COL-ZW). We demonstrate that this conjugat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 32 publications
(43 reference statements)
3
14
0
Order By: Relevance
“…Mice were intravenously administered with CA800Cl (10 nmol, 0.23 mg/kg) or PBS 24 h before laser irradiation and exposed to an 808 nm laser (1.1 W/cm 2 ) for 5 min. Previously, the power density of the 808 nm laser was optimally adjusted to prevent unnecessary damage in normal tissue owing to laser power alone, without any PTT agent [ 23 , 24 ]. The temperature of the tumors treated with CA800Cl markedly increased up to 54.9 °C after 5 min of laser irradiation, whereas tumor temperatures in the PBS-injected mice exhibited minimal change (39 °C) under the same condition ( Figure 5 d).…”
Section: Resultsmentioning
confidence: 99%
“…Mice were intravenously administered with CA800Cl (10 nmol, 0.23 mg/kg) or PBS 24 h before laser irradiation and exposed to an 808 nm laser (1.1 W/cm 2 ) for 5 min. Previously, the power density of the 808 nm laser was optimally adjusted to prevent unnecessary damage in normal tissue owing to laser power alone, without any PTT agent [ 23 , 24 ]. The temperature of the tumors treated with CA800Cl markedly increased up to 54.9 °C after 5 min of laser irradiation, whereas tumor temperatures in the PBS-injected mice exhibited minimal change (39 °C) under the same condition ( Figure 5 d).…”
Section: Resultsmentioning
confidence: 99%
“…To confirm the photothermal properties of ZW800-AM, ZW800-AM (100 µM in PBS) and PBS solutions were individually exposed to 808 nm laser irradiation (1.1 W/cm 2 ) for 1 min. Previously, the power density of an 808 nm laser was determined optimal, capable of avoiding the unnecessary photothermal effect of only laser power, without any PTT agent [26,27]. Temperature changes during the laser irradiation were automatically recorded using an FLIR ® thermal imager as a function of the irradiation time.…”
Section: In Vitro and In Vivo Photothermal Effectsmentioning
confidence: 99%
“…Photothermal therapy (PTT) has great potential in tumor therapy because of its low toxicity to normal tissues and high tumor ablation efficiency [81][82][83]. Sungsu Lee et al [84] reported a study on the tumor targeting property of COL and the advantages of PTT, combining COL with nearinfrared (NIR) fluorescent group ZW800-1 to form a COL-ZW800-1 (Figure 9a) conjugate for targeted cancer imaging and PTT in cancer treatment. The positive charge on COL binds the COL-ZW800-1 conjugate to the outer surface of the negatively charged tumor cell membrane.…”
Section: Antitumor Activitymentioning
confidence: 99%